RECONSTRUCTION OF THE AUTHORITY TO DETERMINE THE CALCULATION OF STATE LOSSES RESULTING FROM CRIMINAL ACTS OF CORRUPTION - A. Muhajir; M. Iman Santoso; Hartanto; Lukman Hakim (Awang Long Law Review, 2026)
The purpose of writing this dissertation is to determine the ideal authority regarding determining the calculation of state losses resulting from criminal acts of corruption. can be reconstructed ideally in the future. The research problem is based on the lack of harmony of norms that lead to the emergence of conflicting norms of laws and regulations related to the understanding of "state losses" with "state financial losses", including the conflict of norms related to "the institution authorized to calculate them". In fact, the calculation of state financial losses and the institution authorized to calculate them are elements of evidence that have a decisive role in handling criminal acts of corruption. This research is a normative legal research with a legislative approach, a conceptual approach, a case approach, and a comparative legal approach. The analysis was conducted using the theory of legal certainty as a grand theory , the theory of criminal responsibility as a middle-range theory , and the theory of authority as an applied theory . Furthermore, these three theories are connected to empirical facts regarding the application of the calculation of state losses by the Supreme Audit Agency (BPK) and other institutions besides the BPK. The research results show that the provisions in various laws and regulations and law enforcement are not sufficient to resolve the existing problems. This is due, among other things, to the lack of compliance of law enforcers, especially the prosecutor's office, in implementing the calculation of financial losses through institutions other than the BPK or at least using calculations from other institutions without a declaration from the BPK. The novelty of this dissertation lies in the effort to reconstruct the norm of state losses into state financial losses regulated in the stages of laws and regulations. Another novelty is to emphasize the authority to determine state financial losses which has been expressly regulated in Article 23C. and 23E paragraph (1) of the 1945 Constitution of the Republic of Indonesia and other statutory provisions which place the BPK as an institution with attributive authority and with a single authority model , which is then introduced in all laws and regulations as long as they are related to law enforcement related to state financial losses, including in the BPK Law, the State Administration Law, the State Treasury Law, the Corruption Crime Law, the Attorney General's Law of the Republic of Indonesia, the Corruption Eradication Commission (KPK) Law and in the Criminal Procedure Code.